2013
DOI: 10.4236/ajps.2013.49205
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Efficient Protocol for the Mass Propagation of <i>Vanilla planifolia</i>

Abstract: The present study describes a direct shoot regeneration-based micropropagation procedure for Vanilla planifolia. Two types of explant (i.e. shoot apex and stem nodal segment) were screened for their shoot induction potential following a three-month treatment with 6-benzylaminopurine (BAP) and -Naphthaleneacetic acid (NAA). Results indicated that the shoot apices were poor candidates for shoot induction whereas the stem nodal segments showed potential for shoot initiation at a rate of up to 6 shoots/explant. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
4
0
6
Order By: Relevance
“…Therefore, there is a need to search for an alternative way to mass produce this plant species. Recently, several studies have reported on the micropropagation of V. planifolia (Tan et al, 2011;Mengesha et al, 2012;Zuraida et al, 2013;De Oliveira et al, 2013). Prior to the present study, the effect of FL on in vitro propagation of vanilla has been reported but no research had been reported using LEDs.…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, there is a need to search for an alternative way to mass produce this plant species. Recently, several studies have reported on the micropropagation of V. planifolia (Tan et al, 2011;Mengesha et al, 2012;Zuraida et al, 2013;De Oliveira et al, 2013). Prior to the present study, the effect of FL on in vitro propagation of vanilla has been reported but no research had been reported using LEDs.…”
Section: Introductionmentioning
confidence: 72%
“…In addition to their unquestionable botanical and ecological importance, orchids participate in current cultivation systems using high-tech horticulture, grown in environments with good climate control, especially temperature, which allows the induction of flowering regardless of the time of year, especially aiming at the scheduled supply of potted and cut flowers in the competitive world flower market. Some species of orchids, such as the genera Dendrobium, Gastrodia, and Bletilla, have also been used for medicinal purposes, using the basis of traditional Chinese medicine [4] and some Vanilla species is also used for food purposes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados de este trabajo en cuanto a la respuesta morfogenética de la longitud del brote, en ausencia de reguladores de crecimiento, fueron muy superiores a los indicados en algunos procedimientos de otros autores (Giridhar y Ravishankar, 2004;Tan et al, 2011b;Zuraida et al, 2013). El promedio logrado (10,54 ± 0,89 cm) no se ha obtenido en protocolos con periodos de evaluación de sesenta días, aún con el uso de reguladores de crecimiento.…”
Section: Discussionunclassified
“…Al respecto, se han obtenido valores de 4,20 ± 0,14 cm al utilizar un medio MS complementado con 1 mg/l BAP (Tan et al, 2011b), 3,8 ± 0,2 cm en un medio MS complementado con 1 mg/l BAP + 0,5 mg/l ANA (Tan et al, 2011a) y 2,9 ± 0,19 cm en un medio MS complementado con 5 mg/l BAP + 1 mg/l AFA (ácido fenilacético) (Giridhar et al, 2003). Otros protocolos similares con un periodo de evaluación de 45 días originaron valores de 4,5 ± 0,14 cm (Zuraida et al, 2013), 2,6 ± 0,1 cm (Giridhar y Ravishankar, 2004) y 3,81 ± 0,33 cm (Giridhar et al, 2001).…”
Section: Discussionunclassified
See 1 more Smart Citation